[OA088] Prostate HDR brachytherapy: the experience of the team matters. (August 2018) - Carrara, Mauro; Giandini, Tommaso; Tenconi, Chiara; Cerrotta, Annamaria; Fallai, Carlo; Pignoli, Emanuele
Abstract : Purpose: To evaluate the learning curve of the BT- team performing prostate HDR brachytherapy (BT) at our Institution. Methods: Since 2010, 108 prostate BT treatments were performed at our Institution by the same BT- team (2 Radiation Oncologists, 2 Medical Physicists), using transrectal ultrasound-guided real time treatment planning. To evaluate the learning curve of the BT- team, Dose Homogeneity Index (DHI) and Conformity Index (COIN) were evaluated. According to the experienced treatment planning difficulties, a new index called Optimal Plan Index (OPI) was also established and evaluated. OPI was defined as the dose to 95% of the prostate (D95%) divided by the dose to 0.1 cc of the urethra (D0.1 cc). The prescribed dose ( D prescr ) was 14 Gy to the prostate surface and the most difficult planning goals were: D95% > 95% D prescr and D0.1 cc < 115% D prescr . The number of needles used for the procedure was also investigated. Results: DHI and COIN didn't show any correlation with the increasing experience of the BT team, whereas OPI resulted to be a good indicator of the learning curve. Average OPI values and number of needles used for the procedure, calculated for every group of 27 patients taken in chronological order, were 0.80 ± 0.05, 0.85 ± 0.06, 0.89 ± 0.03, 0.89 ± 0.02, and 17.6 ± 3.2, 19.4 ± 3.3, 17.2 ± 1.2, 16.8 ± 1.5, for group 1 (G1), 2 (G2), 3 (G3) and 4 (G4), respectively. OPI significantly increased with time (i.e., G1 vs G2 p  < 0.001, G2 vs G3 p  < 0.01, G3 vs G4 p  = 0.67) and number of needles significantly changed over time (i.e., G1 vs G2 p  = 0.02, G2 vs G3 p  = 0.005, G3 vs G4 p  = 0.42), reaching both a plateau and a reduced statistical dispersion after about 50–60 treatments. In fact, within the first 50–60 treatments, some perfectible issues of the procedure were identified and improved (e.g., pre-treatment estimation of pubic arc obstruction, planned and achieved needle positions, dose optimization methods). Attendance of specific courses and conferences helped to achieve this task. Conclusions: The quality of HDR prostate BT is operator dependent and the proposed optimal plan index OPI is a good indicator of the learning curve of a BT- team . OPI and needle analysis, combined with a specific education of the involved clinical personnel, was useful to improve some treatment planning strategies at our Institution.